Quantitative Understanding of Nanoparticle Uptake in Watermelon Plants - Raliya, Ramesh; Franke, Christina; Chavalmane, Sanmathi; Nair, Remya; Reed, Nathan; Biswas, Pratim (Frontiers in Plant Science, 2016)
The use of agrochemical-nutrient fertilizers has come under scrutiny in recent years due to concerns that they damage the ecosystem and endanger public health. Nanotechnology offers many possible interventions to mitigate these risks by use of nanofertilizers, nanopesticides, and nanosensors; and concurrently increases profitability, yields, and sustainability within the agricultural industry. Aerosol based foliar delivery of nanoparticles may help to enhance nanoparticle uptake and reduce environmental impacts of chemical fertilizers conventionally applied through a soil route. The purpose of this work was to study uptake, translocation, and accumulation of various gold nanostructures, 30 to 80 nm, delivered by aerosol application to a watermelon plant. Cellular uptake and accumulation of gold nanoparticles were quantified by Inductively Coupled Plasma-Mass Spectroscopy (ICP-MS). Observations suggested that nanoparticles could be taken up by the plant through direct penetration and transport through the stomatal opening. Observed translocation of nanoparticles from leaf to root shows evidence that nanoparticles travel by the phloem transport mechanism. Accumulation and transport of nanoparticles depend on nanoparticle shape, application method, and nature of plant tissues.